PENGARUH CITRA DESTINASI DAN MOTIVASI WISATAWAN TERHADAP LOYALITAS WISATAWAN MELALUI KEPUASAN WISATAWAN - Imam, Herdin; Ningrum, Nonik Kusuma; Hutami, Lusia Tria Hatmanti (Jurnal Pendidikan Ekonomi (JURKAMI), 2025)
The competition of tourist destinations in the Special Region of Yogyakarta (DIY) is getting tighter, encouraging managers to improve the quality of facilities and infrastructure to attract tourists. This study examines the influence of destination image, tourist motivation, and tourist satisfaction as intervening variables on tourist loyalty. This study is quantitative by taking 160 samples from tourists visiting tourist destinations in DIY. Sampling was carried out using a non-probability method and using a sampling technique, namely purposive sampling. Data collection was carried out online by sending a questionnaire link to respondents. Data were analyzed using the IBM SPSS application. The results of the study showed that destination image and tourist motivation had a significant effect on tourist satisfaction, while satisfaction and destination image had a significant effect on tourist loyalty. However, tourist motivation did not have a direct effect on loyalty, although its role was mediated by tourist satisfaction. The implication of this study is the importance of improving destination image through promoting local uniqueness and service quality and prioritizing a satisfying tourist experience. Although motivation does not have a direct effect, understanding tourist needs can indirectly strengthen loyalty. With a satisfaction-based strategy, DIY tourist destinations can increase competitiveness and encourage tourist loyalty in a sustainable manner.